Are more severe recessions followed by stronger recoveries? Evidence from the Mexican states employment - Pablo Mejía-Reyes; Reyna Vergara-González (European Regional Science Association (ERSA), 2015)
On the basis of the suggestions of Friedman (1969, 1993) and Moore (1965) and considering the framework proposed by Balke and Wynne (1994, 1995), this paper evaluates whether recoveries growth depends on the characteristics of prior recessions (depth, steepness and duration) in the case of the Mexican states employment during the 2001-2003 and 2008-2009 recessions. The original models are extended to include the effects of external and fiscal shocks, as measured by the annual growth rates of the tradable goods production sector and the federal government expenditure of the year the recoveries start, trying to capture the initial impulses that may have taken the economy out the recession. The recession and recovery periods (turning points, namely peaks and troughs) are identified by using the classical business cycles methodology introduced by Artis, Kontolemis and Osborn (1998) that follows the spirit of Mitchel (1927) and Burns and Mitchel (1946). Recoveries growth is measured as the monthly average growth rate from the end of the prior recession up to 9, 12 and the number of months required to get the prior peak. Conventional linear regression models are estimated for total, permanent and temporary employment. To avoid possible problems of collinearity between depth and duration, on the one hand, and steepness, on the other, these variables were included in two different specification models for each type of employment. The corresponding tests indicate that the estimated models present acceptable specifications, in general. Our main results suggest that depth and steepness of prior recessions (as measured by the percentage accumulated drop and the monthly average growth rate of employment over the recession, respectively) have separated negative effects on subsequent growth recoveries, especially after the 2001 recession. Regarding the effects of other shocks pulling the economy out the recession, our results suggest that the fiscal policy followed by the federal government did not contribute to the recovery from the 2008 recession at state level since the coefficients are negative, which would imply the existence of a pro-cyclical policy at least at the end of the recession period. In turn, in the models of total and permanent employment, the tradable goods sector has robust positive and significant effects that reflect the important role of the external demand in the recovery from the Great Recession. These two variables had no significant effects of the recovery following the 2001 recession. In general, the evidence reported in this paper is consistent with the implications of different models that try to explain the ?bounce-back? effect and provides some support to the hypothesis that deeper or steeper recessions are followed by stronger recoveries in the Mexican states.
Keywords: E24; E32; R11; E39; 330; Employment; Regional business cycles; Recessions; Recoveries